INFRASTRUCTURE DIPLOMACY AS A TOOL OF SUSTAINABLE DEVELOPMENT: A GEOPOLITICAL DIMENSION - Simonov, Mykyta (Current Problems of Sustainable Development, 2026)
The article examines the phenomenon of infrastructure diplomacy and its instrumental significance as a means of sustainable development in the context of geopolitical influence and strategic competition between leading global actors. The evolution of geopolitical thought from the classical territorial concepts of Mackinder, Mahan, and Spykman to the modern infrastructure turn, in which control over infrastructure becomes a defining dimension of international influence, is analyzed. The analysis considers four key global strategies: the Chinese Belt and Road Initiative (BRI), the EU Global Gateway Initiative, and the Blue Dot Network (BDN), Partnership for Global Infrastructure and Investment (PGII) pursued by the US and its allies. A comparative analysis of these initiatives is carried out according to the criteria of financial volume, type of financing, regulatory conditions, speed of implementation, and geopolitical goals. It is substantiated that modern infrastructure functions as a mechanism for the formation of long-term dependencies, standardization, and projection of soft power. The significance of the Global Gateway initiative for Ukraine in the context of reconstruction and the European integration course is separately considered.